2018
DOI: 10.1029/2018jd028360
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing Physical Mechanisms Leading to Pure Heat Waves Versus Pure Tropical Nights Over the Korean Peninsula

Abstract: This study analyzes differences in the mechanisms leading to anomalously high‐temperature weather events, such as heat waves and tropical nights, in Korea. We identify pure heat wave and pure tropical night events during the period from 1979 to 2016. Based on composite analyses for each case, we identify different mechanisms leading to pure heat waves and pure tropical nights. The structures including low‐level atmospheric circulations, specific humidity, wind, and the atmospheric stability are quite different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
37
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 37 publications
7
37
0
Order By: Relevance
“…6c). These features are similar to the vertical atmospheric structure associated with the KP HWs suggested by Hong et al (2018). They also emphasize the roles of the anomalous high in the upper and lower levels accompanied by anomalous easterly winds around the KP.…”
Section: Seasonal Evolution Of Stationary Wavessupporting
confidence: 80%
“…6c). These features are similar to the vertical atmospheric structure associated with the KP HWs suggested by Hong et al (2018). They also emphasize the roles of the anomalous high in the upper and lower levels accompanied by anomalous easterly winds around the KP.…”
Section: Seasonal Evolution Of Stationary Wavessupporting
confidence: 80%
“…After 1994 heat wave event, most extreme heat waves in Korea occurred in recent years, such as August 2013, August 2016, and July‐August 2018. Hong et al () also reported the significant increasing trend in frequency of heat wave occurrence over Korea for the period of 1979‐2016. Considering the increasing number of extreme heat waves over Korea in recent years and their widespread impacts, it is important to understand physical processes of heat waves in Korea and improve their predictability.…”
Section: Introductionmentioning
confidence: 91%
“…This partly explains why extreme hot events fail to persist through day and night as they do during compound hot extremes. A diurnal cycle of anomalous anticyclones during independent hot extremes was also reported in other studies focusing on events in other regions (Kueh et al ., 2017; Hong et al ., 2018). Moreover, during independent hot days and nights, there is no clear signal of paired anomalous diabatic heating in both the north and south of the Yangtze River Valley, as observed during compound hot extremes.…”
Section: Resultsmentioning
confidence: 99%
“…Certain large‐scale atmospheric and oceanic modes such as the transition phase from El Nino to La Nina and the North Atlantic Oscillation, were also found favourable to the occurrence of summertime hot extremes in various regions (Cassou et al ., 2005; Chen et al ., 2018). A recent study distinguishes daytime‐only and nighttime‐only hot extremes on the Korea Peninsula, and found that anomalies in circulation patterns and solar radiation play a joint role in determining the event type (Hong et al ., 2018). In addition, local topography and region‐specific land‐atmosphere interactions can also lead to extreme high temperature events (Vogel et al ., 2018).…”
Section: Introductionmentioning
confidence: 99%